The Prognostic Value of Initial Tumor Size in Patients with Ewing Family of Tumors - Deo, Rajeeb Kumar; Chitalkar, Prakash; Joshi, Amit; Ranamagar, Sushil (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Ewing Family of Tumors (EFT) is a high grade embryonic malignancy, common in children andyoung adults (CYAs). The prognostic factors include initial tumor volume, site, presence of metastasis, and theEWS/FLI 1 mutation. Low volume disease is known to result in higher response rates and longer survival times. Methods: Twelve patients with non-metastatic EFT were managed with the intensive Ewing Family Tumor(EFT 2001) protocol. The patient characteristics studied were - age, sex, site, number of sites involved,bone marrow involvement and size (volume). Tumor volume was measured in non-metastatic tumors by tridimensionalvolume in MRI scans. Results: Progression free survival (PFS) of patients with initial tumor volume ????100 cc ranged from 30 monthsto 74 months (mean 56.4 months) while that for > 100 cc ranged from 19 months to 79 months (mean 40months) (p value: 0.701). However there was trend towards better survival in patients with initial tumor volume????100 cc. Conclusions: There is a trend towards better PFS in patients with smaller tumor volume at presentation. Thusinitial tumor volume is a prognostic factor in Ewing family of tumors. doi:http://dx.doi.org/10.3126/mjsbh.v12i2.12925